Revitalization and action research = Rewitalizacja a badania w działaniu - Gheondea-Eladi, Alexandra (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The revitalization of public spaces and buildings has evolved to be a process in which the community and the residents of an area are actively involved in the process of changing and developing spaces and buildings of interest. In this way revitalization of public spaces comes very close to the empowerment goals of action research.
Keywords: rewitalizacja; partycypacja; empowerment; praktyki; badania w działaniu; revitalisation; participations; practice; action research